Capra cartilage-derived peptide delivery via carbon nano-dots for cartilage regeneration - Maity, Priti Prasanna; Kapat, Kausik; Poddar, Puja; Bora, Hema; Das, Chandan Kanta; Das, Poushali; Ganguly, Sayan; Das, Narayan Chandra; Dhara, Dibakar; Mandal, Mahitosh; Roy Chowdhury, Amit; Mukherjee, Sumanta; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Targeted delivery of site-specific therapeutic agents is an effective strategy for osteoarthritis treatment. The lack of blood vessels in cartilage makes it difficult to deliver therapeutic agents like peptides to the defect area. Therefore, nucleus-targeting zwitterionic carbon nano-dots (CDs) have immense potential as a delivery vehicle for effective peptide delivery to the cytoplasm as well as nucleus. In the present study, nucleus-targeting zwitterionic CDs have been synthesized as delivery vehicle for peptides while also working as nano-agents towards optical monitoring of cartilage healing. The functional groups of zwitterion CDs were introduced by a single-step microwave assisted oxidation procedure followed by COL II peptide conjugation derived from Capra auricular cartilage through NHS/EDC coupling. The peptide-conjugated CDs (PCDs) allows cytoplasmic uptake within a short period of time ( 30 m) followed by translocation to nucleus after 24 h. Moreover, multicolor fluorescence of PCDs improves (blue, green, and read channel) its sensitivity as an optical code providing a compelling solution towards enhanced non-invasive tracking system with multifunctional properties. The PCDs-based delivery system developed in this study has exhibited superior ability to induce ex-vivo chondrogenic differentiation of ADMSCs as compared to bare CDs. For assessment of cartilage regeneration potential, pluronic F-127 based PCDs hydrogel was injected to rabbit auricular cartilage defects and potential healing was observed after 60 days.2 Therefore, the results confirm that PCDs could be an ideal alternate for multimodal therapeutic agents.